2021
DOI: 10.3389/fimmu.2021.736349
|View full text |Cite
|
Sign up to set email alerts
|

Systems Biology to Understand and Regulate Human Retroviral Proinflammatory Response

Abstract: The majority of human genome are non-coding genes. Recent research have revealed that about half of these genome sequences make up of transposable elements (TEs). A branch of these belong to the endogenous retroviruses (ERVs), which are germline viral infection that occurred over millions of years ago. They are generally harmless as evolutionary mutations have made them unable to produce viral agents and are mostly epigenetically silenced. Nevertheless, ERVs are able to express by still unknown mechanisms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…Therefore, improving our knowledge of TEs through deep genomic approaches may lead to new potential diagnostic markers of diseases and prenatal markers of genetic diseases. Thus, the development of combined molecular (i.e., next generation sequencing and whole genome sequencing) and bioinformatics tools is of great interest despite mostly used in the cancer field [ 32 , 34 , 50 , 55 , 56 , 113 , 130 , 167 , 168 , 169 ]. Finally, the exposure of individuals to numerous stresses and in particular to environmental pollutants and contaminants seems to have a non-negligible impact on the epigenetic derepression and mobility of TEs, which can lead in this way to the development of certain pathologies such as cancers, neurological or autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, improving our knowledge of TEs through deep genomic approaches may lead to new potential diagnostic markers of diseases and prenatal markers of genetic diseases. Thus, the development of combined molecular (i.e., next generation sequencing and whole genome sequencing) and bioinformatics tools is of great interest despite mostly used in the cancer field [ 32 , 34 , 50 , 55 , 56 , 113 , 130 , 167 , 168 , 169 ]. Finally, the exposure of individuals to numerous stresses and in particular to environmental pollutants and contaminants seems to have a non-negligible impact on the epigenetic derepression and mobility of TEs, which can lead in this way to the development of certain pathologies such as cancers, neurological or autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these authors observed TE dysregulation in the alveolar type II lung cells and alveolar macrophages of IPF patients and the increased TE, especially LINE-1, expression is positively correlated with both the activation of cellular TE inhibitors and the innate immune response and negatively correlated with autophagy in IPF [ 129 ]. The involvement of HERVs in innate immunity has been also demonstrated and HERVs contribute to pro-inflammatory diseases such as Type-I diabetes, autoimmune disorders and multiple sclerosis, as well as neuropathogenesis of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) [ 130 ]. Finally, the mutual interaction between microbiote and HERVs expression was highlighted in humans by a strong correlation between the expression of HERV-H, -K and -W, and the concentration of Bifidobacterium spp.…”
Section: Involvement Of Tes In Non-cancerous Pathologies and Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Human endogenous retroviruses (HERVs) are found in human genomes because of retrovirus integration over millions of years ago. 8 Ancient HERV elements contribute to human genomic innovation and human evolution and have recently been identified as regulators in various pathophysiological processes, such as immune-related diseases, cancers, and neurological disorders. 9 Lysine demethylase 1A (LSD1/KDM1A) is reported to negatively regulate HERV transcripts and their intracellular double-stranded RNA (dsRNA), which is one type of PAMPs stimulating IFNβ producion.…”
Section: Introductionmentioning
confidence: 99%
“…Human endogenous retroviruses (HERVs) are found in human genomes because of retrovirus integration over millions of years ago 8 9 .…”
Section: Introductionmentioning
confidence: 99%